Material efficient process for producing lightweight tubular screws and nuts. (1st November 2016) - Alves, L.M.; Silva, C.M.A.; Martins, P.A.F.
Abstract: This paper proposes a new material efficient process for producing lightweight tubular screws and nuts. The process is built on the fundamentals of tube end forming and combines tube reduction, expansion, flaring and compression beading to establish two multi-stage cold forming sequences for producing hexagon head tubular screws and nuts. The methodology draws from the mechanical characterization of the material to the design and fabrication of an experimental apparatus consisting of several individual die sets. The investigation is supported by finite element modelling and it is aimed at evaluating the major process parameters, the overall feasibility of the process and the required forming loads. Highlights: Material efficient cold forming process for producing tubular screws and nuts. Potential to replace conventional screws and nuts in lightweight applications. Numerical and experimental characterization of the deformation mechanics and process window.